Winter - Sharp, Dallas Lore, 1870-1929; Horsfall, R. Bruce (Robert Bruce), 1869-1948 (Salt Lake City, UT : Project Gutenberg, 2013)
"Winter" by Dallas Lore Sharp is a nature writing book crafted in the early 20th century. This work beautifully captures the essence of the winter season, exploring its challenges and beauty through a series of engaging stories and descriptions of wildlife. Sharp's vivid imagery introduces readers to the life and rhythm of nature during winter, invoking a profound appreciation for the season's unique qualities. At the start of the book, the introduction emphasizes the spirit of winter as a symbol of vitality and perseverance, contrasting the deceptive stillness of the season with the life it sustains beneath the surface. In the first chapter titled "Hunting the Snow," Sharp recounts an adventure with children as they embark on a playful "hunt" after the first snowfall, emphasizing the excitement of tracking animal footprints rather than hunting for game. The narrative effectively paints a lively picture of the snowy landscape as the children eagerly explore their surroundings, discovering the hidden narratives of wildlife through the tracks left in the snow. (This is an automatically generated summary.)
Release date is 2013-02-28
E-text prepared by Greg Bergquist, Matthew Wheaton, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://archive.org/details/americana)
Keywords: Natural history -- Outdoor books